Motherhood, Migration, and Self-Employment of College Graduates - Zhengyu Cai; Heather M. Stephens; John V. Winters (Institute of Labor Economics (IZA), 2019)
Women face unique challenges in starting and running their own businesses and may have differing motives to men for pursuing self-employment. Previous research suggests that married women with families value the flexibility that self-employment can offer, allowing them to balance their family responsibilities with their career aspirations. This may be especially true for college graduates, who tend to have more successful businesses. Access to childcare may also affect their labor force decisions. Using American Community Survey microdata, we examine how birth-place residence, a proxy for access to extended family and child care, relates to self-employment and hours worked for college-graduate married mothers. Our results suggest that flexibility is a major factor pulling out-migrant college-educated mothers into self-employment. Additionally, it appears that, in response to fewer childcare options, self-employed mothers away from their birth-place work fewer hours, while self-employed mothers residing in their birth place are able to work more hours per week.
Keywords: J13; J22; L26; 330; motherhood; migration; self-employment; childcare; hours worked